Is There Any Indication for an Intracardiac Defibrillator for the Treatment of Atrial Fibrillation? - Lévy S; Richard P (Journal of Cardiovascular Electrophysiology, 1994)
ICD for Treatment of AF. The experience gained using intracardiac cardioverter defibrillators for the treatment of ventricular arrhythmias has prompted the development of an automatic atrial defibrillator capable of detecting and automatically terminating atrial fibrillation (AF). Experimental studies in sheep have shown that it is possible to terminate AF with energies ranging from < 1 to 7 joules [J], using biphasic shocks. The best electrode configuration using intra-cardiac catheters and/or a subcutaneous patch was two catheters, one in the right atrium and the other in the coronary sinus. Current studies in man focus on the answers to three questions. First, can the experimental results of atrial defibrillation derived from healthy anesthetized sheep with-out spontaneous AF be extrapolated to AF in man with areas of fibrosis within the atria and/or underlying heart disease in 80% of cases? Preliminary studies in man suggest that cardioversion of AF of short duration is feasible using a mean energy of 2 J. Second, are these energies well tolerated in an awake nonsedated patient? Energies < 1 J were well tolerated, but pain resulting from higher energies needs further investigation. Third, is low-energy atrial defibrillation safe, i.e., is there a risk of ventricular arrhythmias induced by an atrial shock? Experimental results in sheep have shown that the risk of R wave synchronized shock to induce ventricular arrhythmias was only present when the preceding RR interval was shorter than 300 msec. The risk of proarrhythmia in man is undergoing evaluation and must be sufficiently low (< 0.1) before sanctioning implantation of a stand-alone (without associated ventricular defibrillator) automatic atrial defibrillator. Preliminary data on 1212 shocks showed no proarrhythmia. There is definitely a significant group of patients with attacks of AF (Class IIIB or IIIC) that are resistant to antiarrhythmic therapy. Another group of symptomatic patients may have infrequent attacks, or poorly tolerated (syncope or heart failure) or long-lasting attacks requiring medical intervention and/or hospitalization (Class IB, IIB), for whom an automatic atrial defibrillator may be a valuable option. The alternative therapies could be either catheter ablation of the AV node with implantation of a pacemaker or selective surgery. Most of the technical problems related to AF detection and reliable atrial defibrillation have been solved. However, clinical investigations are needed to evaluate the efficacy and safety of this new and exciting therapeutic modality.